2005
DOI: 10.1088/0022-3727/38/22/018
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of SnPb and lead-free solders at high rates of strain

Abstract: The mechanical properties of 63% Sn–37% Pb and lead-free solders have been measured at high strain rates (500–3000 s−1) using a split Hopkinson pressure bar. The solders were produced by quenching in water from the melt, to give the phase structure associated with rapid cooling. Measurements were made at −40 °C, room temperature and +60 °C. The Sn–Pb solder was strongly strain rate and temperature dependent, whereas the lead-free solders showed only a weak dependence on these parameters. All of the materials b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…Figure 16 shows typical loading curves of 0.76-mm virgin solder balls at two different compression rates-a slow rate of 3.6 × 10 −5 m/sec and a high rate of 12.5 m/sec for each solder composition. Similar data on lead-free solder balls were reported by Siviour et al at 8 m/sec [35]. Since they are spheres and not cylindrical specimens with uniform crosssectional area), force-displacement curves are shown instead of stress-strain curves.…”
Section: Mechanical Properties Of Sn-37pb Sn-35ag and Sn-38ag-07supporting
confidence: 69%
See 2 more Smart Citations
“…Figure 16 shows typical loading curves of 0.76-mm virgin solder balls at two different compression rates-a slow rate of 3.6 × 10 −5 m/sec and a high rate of 12.5 m/sec for each solder composition. Similar data on lead-free solder balls were reported by Siviour et al at 8 m/sec [35]. Since they are spheres and not cylindrical specimens with uniform crosssectional area), force-displacement curves are shown instead of stress-strain curves.…”
Section: Mechanical Properties Of Sn-37pb Sn-35ag and Sn-38ag-07supporting
confidence: 69%
“…An extensive list of references pertaining to the study of the SHPB can also be found in a review by Field et al [58]. Wang et al [25] and Siviour et al [35] obtained strain rates reaching up to a maximum of 3000 sec −1 from SHPB experiments on solder material. However, numerical simulation by Ong [59] shows that certain parts of the solder balls will experience higher strain rates (close to 10,000 sec −1 ) when the solder balls are compressed at a deformation rate of approximately 5 m/sec.…”
Section: Dynamic Materials Properties Of Solder Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…For isothermal samples, the grain size is uniform across the solder joint according to this relation, and accordingly there is no gradient of hardness. Lead-free solder alloy, including SAC, has been shown to follow Hall-Petch relation (Siviour et al, 2005). For SnPb solder, nanoindetation results from Ye et al (2004) show that the mechanical properties are in agreement with the Hall-Petch relation.…”
Section: Discussionmentioning
confidence: 76%
“…Young's Modulus E = (57.7-0.056T) GPa (Hong, 1998), Poisson ratio m = 0. 33 Hong, 1998, Yield stress r y = (140.67-0.2133T) MPa (Siviour et al, 2005), Equilibrium Vacancy concentration at a stress free state is 1.107 Â 10 6 lm À3 (Ye, 2004;Balzer and Sigvaldason, 1979), vacancy relaxation time is 0.0018 s (Sarychev et al, 1999), average vacancy relaxation ratio is 0.2 (Sellers et al, 2007;Bassman, 1999). The thermal properties are listed in Table 1.…”
Section: Finite Element Analysismentioning
confidence: 99%